2018
DOI: 10.1002/ldr.3014
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: Reconciling interpretations of forest landscape restoration

Abstract: Although forest restoration is not a new concept, it has recently gained in popularity.Forest landscape restoration (FLR) in particular may be said to have acted as an ambassador for the wider restoration cause. Yet how different communities and disciplines interpret this complex term has implications for their implementation decisions. Although the term FLR is used widely, it signifies different things to different people. Ambiguity may prove to be both an asset and a liability. The objective of this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…climate resilience, food and water security, biodiversity conservation). FLR has been interpreted in different ways (Mansourian ) leading to different constructs of FLR (e.g. safeguarding biodiversity, reducing land degradation, supporting sustainable timber production).…”
Section: Section 4—leading Practicesmentioning
confidence: 99%
“…climate resilience, food and water security, biodiversity conservation). FLR has been interpreted in different ways (Mansourian ) leading to different constructs of FLR (e.g. safeguarding biodiversity, reducing land degradation, supporting sustainable timber production).…”
Section: Section 4—leading Practicesmentioning
confidence: 99%
“…An understanding of what comprises land and forest degradation, and preferences for management scenarios, can depend on individuals' backgrounds and value systems; a social scientist may perceive the landscape differently than an ecologist, or an industrial business person's view may differ from that of a small‐scale subsistence farmer (Carmenta, Zabala, Daeli, & Phelps, ; Mansourian, ). The multiplicity of interests in forests—as an object of exploitation, a basis for local livelihoods, as biodiversity‐rich ecosystems, as places for climate change mitigation and adaptation, and a global resource to protect, manage, and restore—spans many disciplines, sectors, and actors (Baker, Eckerberg, & Zachrisson, ; Mansourian, ). For example, forest scientists and ecologists have sought to understand the dynamics of forest ecosystems to restore ecosystem functions on degraded forest lands and improve habitat quality for key species (Higgs, ; Hobbs & Norton, ; Lamb, Erskine, & Parrotta, ; Palmer, Falk, & Zedler, ), whereas development organisations have seen restoration as a tool to reverse land degradation, enhance rural livelihoods, supply communities with fuelwood and other forest products, improve water and soil quality, and protect agricultural fields and coastlines (MEA, ).…”
Section: Integration Challenges For Flrmentioning
confidence: 99%
“…Yet, there is surprisingly little collaboration among scientists, FLR planners, practitioners, and policymakers (Mansourian, ; Riggs et al, ). There is also little cross‐disciplinary use of knowledge from relevant forestry and non‐forestry disciplines.…”
Section: Integration Challenges For Flrmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the literature on rewilding, like the literature on wilderness, highlights the confusion at what, at first glance, may appear to be quite clear terminology (Hall & Page, 2014). Indeed, as with the wilderness concept rewilding also potentially becomes problematic when it comes to its operationalisation (Corlett, 2016;Jørgensen, 2015;Koninx, 2018;Lorimer et al, 2015;Lorimer & Driessen, 2013Mansourian, 2018;Svenning et al, 2016). For example, in a study of wildland managers in the Scottish uplands Deary and Warren (2019) found that all managers valued wildness and biodiversity highly but that there was significant divergence in the interpretations and practices of rewilding, especially with respect to: the value and perceptions of naturalness, the use of management interventions, the value of cultural heritage and traditional land uses, and the place of people within wildland.…”
Section: Definition and Issuesmentioning
confidence: 99%